The putative effect of a SOD-rich melon pulp-concentrate on growth performance and antioxidant status of Nile tilapia (Oreochromis niloticus) under heat/dissolved oxygen-induced stress - Xavier, William dos Santos [UNESP]; Leclercq, Eric; Carvalho, Pedro Luiz Pucci Figueiredo [UNESP]; Vicente, Igor Simões Tiagua [UNESP]; Guimarães, Matheus Gardim [UNESP]; Rodrigues, Edgar Junio Damasceno [UNESP]; Milanezi, Rafael Colauto [UNESP]; Barbé, Florence; Sartori, Maria Márcia Pereira [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Barros, Margarida Maria [UNESP] (Elsevier, 2020)
This study evaluated the effects of SOD-rich melon pulp concentrate (MPC) premix on growth performance, hematological profile and the antioxidant capacity of Nile tilapia (Oreochromis niloticus) subjected to heat/dissolved oxygen-induced stress (HDOIS). A group of 462 male Nile tilapia (8.87 ± 0.12 g) was randomly distributed in 42,250-L tank (11 fish/tank) and fed seven practical diets supplemented with graded levels of MPC (0.0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% and 1.0% MPC premix of diet; PM Melofeed 2.5, SOD activity min. 65,000 IU kg−1, Lallemand SAS, Blagnac, France) with six replicate tank/diet. The diets were formulated to contain 30% crude protein and 18 MJ kg−1 crude energy. After 60 days of feeding, growth performance was evaluated and six fish per treatment were sampled for hematological profile and analysis of the hepatic activity of key antioxidant enzymes. Then, remaining fish were subjected to HDOIS (34 °C/1.87 mg L−1 dissolved oxygen) for 2 days and the same hematological profile and antioxidant enzyme activities were determined. MPC supplementation was associated with the recruitment of hepatic antioxidant defense in the form of increased SOD activity prior and after HDOIS as well as of GR activity before HDOIS at 0.4% MPC and above. These levels of MPC supplementation were weakly associated with reduced level of muscle lipid oxidation. This trial indicates that MPC supplementation at or above 0.4% contributes to a better maintenance of antioxidant defense in Nile tilapia when exposed to HDOIS environmental stress. This is expected to yield biological benefits in the longer-term when Nile tilapia are chronically or repetitively exposed to similar environmental stressors as may be the case under intensive aquaculture conditions.
Keywords: Hematological profile; Hepatic antioxidant enzymes; In-feed primary antioxidant; Oreochromis niloticus; Oxidative stress; Stress